Combined educational and contraceptive interventions reduce unplanned teenage pregnancy, but how useful is this finding for policy and practice?. Issue 1 (22nd February 2010) - Fletcher, Adam
Abstract : Commentary on: Oringanje C Meremikwu MM Eko H . Interventions for preventing unintended pregnancies among adolescents . Cochrane Database Syst Rev 2009 :CD005215.